Activities of Transmitted/Founder and Chronic Clade B HIV-1 Vpu and a C-Terminal Polymorphism Specifically Affecting Virion Release - Jafari, Moein; Guatelli, John; Lewinski, Mary K. (Journal of virology, 2014)
Acute HIV-1 infection is characterized by a type I interferon response, resulting in the induction of host restriction factors. HIV-1 has evolved to counteract these factors, and one such adaptation, the ability of Vpu to counteract BST2/tetherin, is associated with the evolution of simian immunodeficiency virus (SIV cpz ) into pandemic group M human immunodeficiency virus type 1 (HIV-1). During transmission between individuals, very few viruses or even a single virus, the “transmitted/founder” (T/F) virus, gives rise to the new infection, but in the new host the selective pressure of the immune response yields the diverse “quasispecies” of chronic infection. Here we examine the functional characteristics of Vpu proteins encoded by T/F viruses compared to acute and chronic viruses from longitudinally sampled subjects. The studied T/F Vpu proteins showed a trend toward optimized CD4 downregulation compared to chronic Vpu proteins but did not differ substantially in their ability to downregulate BST2 or enhance virion release, although individual clones from each group were impaired in these activities. Analysis of the functionally impaired clones identified a C-terminal residue, W76, as important specifically for Vpu enhancement of virion release. Primary Vpu clones encoding a W76G polymorphism, or site-directed mutants encoding a W76G substitution, were impaired in their ability to enhance virion release, but they were not defective for BST2 surface downregulation. Conversely, the virion release function of impaired primary clones was restored by creating a G76W substitution. The identification of W76 as important for virion release enhancement that is independent of BST2 surface downregulation supports the potential to mechanistically separate these functions of Vpu. IMPORTANCE To establish infection in a host, HIV-1 must evade the host's immune response, including the production of antiviral factors. HIV-1 encodes proteins that antagonize these defenses, including Vpu. Vpu counteracts the host protein BST2, which blocks the release of progeny viruses from the host cell. To determine the importance of Vpu activity to HIV-1 transmission, this study assessed the functionality of Vpu from viruses isolated soon after transmission (“transmitted/founder” viruses) compared to isolates from chronic infection. Although the anti-BST2 activity of Vpu proteins from the tested transmitted/founder viruses did not differ from the activity of the chronic Vpu proteins, the transmitted/founder Vpu proteins trended toward having superior activity against another host protein, CD4. Further, this study identified an amino acid near the C terminus of Vpu that is specifically important for Vpu's ability to enhance the release of progeny virus from the host cell, supporting the notion of a new mechanism for this function of Vpu.